튜닝포크를 이용한 액체밀도의 계측 - 김충현; 이용복; 이성철 (한국생산제조학회, 2007)
A sensor using quartz tuning fork is presented for measuring liquid density. It consists of a PZT plate as an actuator for piezoelectric excitation and a quartz tuning fork as a sensor for resonant frequency detection. The resonant frequency is determined from the sensing voltage measured in tuning fork when the excitation frequencies of PZT actuator are swept around the resonant frequencies of tuning fork. The resonant frequency determined the liquid density. The density values of three kinds of organic solvents are measured and compared with the standard values. The experimental results are in agreement with the standard values and the maximum standard deviation is less than 9%.